Coryanthes charlesiana (Stanhopeinae, Cymbidieae, Orchidaceae), a new species from Brazil - Chiron, Guy R.; Marçal, Sidney (Phytotaxa, 2022)
A new species of Coryanthes, from the State of Alagoas in Brazil, is proposed. It comes from Atlantic Forest and only one plant has been studied, in the municipality of Atalaia. This find represents the first occurrence of a Coryanthes member in Alagoas. The new taxon is characterized by its smooth mesochile (i.e. it belongs to the subgenus Coryanthes) and its hairy hypochile, what is not common in the subgenus. It is described, illustrated and compared to its closest relative, Coryanthes lanata. Moreover a key to all the pubescent species of the subgenus is provided.